Effect Of Different Percentages Of Biodiesel-Diesel Blends On Combustion, Performance And Emission Characteristics Of Diesel Engine - Shahidan, Muhammad Danish Haziq (Universiti Sains Malaysia, 2017)
A comparative study of effect of different percentages of biodiesel-diesel blends (B20, B45 and base diesel) on performance, emission and combustion at nine different speed (1600, 1800, 2000, 2200, 2400, 2600, 2800, 3000 and 3200) was carried out. The engine torque for B45 shows the highest compared with B20 and base diesel. However, the torque reduce at high speed for every biodiesel-diesel blend and base diesel. Carbon monoxide (CO), hydrocarbon (HC) and smoke emissions decreased will all biodiesel-diesel blends. However, nitrogen oxide (NO) emission increase at 2600 rpm for all biodiesel-diesel blends and base diesel due to oxygenated fuel, automatic dynamic injection timing (DIT), higher penetration and higher temperature. The ignition delay period decreased as increase the biodiesel percentage due to high cetane number. Besides, the pressure rise was low as cetane number increased so engine running smoothly.